Interactive intervention strategy for English as a foreign language classes versus traditional methods to teach speaking - Amjad Alsyouf; Murad Al Kayed (Universitas Syiah Kuala, 2021)
This paper proposes Interactive Intervention Strategy (IIS) as an effective activity to teach English as a Foreign Language (EFL) in the Arab world and other similar EFL environments. It explores the impact of IIS on the speaking skills (fluency, pronunciation, vocabulary, and grammar) of EFL students in the Jordanian context. The study used a quasi-experimental quantitative design to analyze the data. The sample of the study consisted of 30 students as a control group and 30 students as an experimental group. Both groups were enrolled in a speaking course in their first semester. The study employed an interview post-test to evaluate the effectiveness of IIS in teaching speaking skills. IIS is sought in this context to excite the minds of the learners with target subjects using untraditional techniques. It is designed to help in eliminating L2 learners’ confusion and increasing their motivation by adapting the activities of the traditional teaching environment. IIS is thus proposed as a strategy that challenges the traditional approaches to teaching EFL in helping the learners to use English as a communicative language through developing extra-class interactive sessions demonstrated to support EFL speaking classrooms.